ANTHROPOMETRY AND BODY COMPOSITION OF THE SOCCER REFEREE (Fiep Bulletin - online, 2014)
The soccer referee is the authority that makes the game rules to be fulfilled. He supervises, judges and applies the penalties to the players. The performance of his function demands that he has minimal fitness in order to follow the game with a good angle of vision, free of any psychological or physical stress. However, for establishing training programs it is necessary to know the adequate anthropometric profile for this function, beside the physical requirements of this activity. The aim of this study is determine the anthropometric and body composition profiles of the soccer referees of the Federação Paranaense de Futebol (Soccer Federation of Paraná) during the 2000 season. The sample was constituted by 87 referees, which were intentionally choosen. Nine skin folds, 9 perimeters and 4 bone diameters were measured, besides body mass and height. The body density, the fat percent and the masses of fat, bone, residues and muscles were determined using the anthropometric variables. The results of this study lead us to conclude that the soccer referees of the Federação Paranaense de Futebol present a mean age of 32.9  4.8 years, height of 175.4  6.9 cm, and corporal mass of 75.4  9.1 kg. With regard to the body composition data, the mean fat percent was 16.3  4.1%. The results of this study are very similar to the values of the normal population, but higher than the values of younger populations, as university students and soldiers. All other variables of the body composition, as bone and muscular masses, follow this tendency of being closer to the mean normal man and of having a disadvantage regarding younger populations. All these data lead us to conclude that the soccer referee of the Federação Paranaense de Futebol has an anthropometric profile characteristic of the median man with an age of 30 years.
Keywords: anthropometry; referee; soccer